Finding a Path to Formalization in Benin : Early Results after the Introduction of the Entreprenant Legal Status - Benhassine, Najy (World Bank, Washington, DC, 2015)
In April 2014, the Government of Benin launched the entreprenant status, a simplified and free legal regime offered to small informal businesses to enter the formal economy. This paper presents the short-term results of a randomized impact evaluation testing three different versions of the entreprenant status on business registration decisions, each version including incremental incentives to registration: (i) information on the new legal status and its benefits, (ii) business training, counseling services, and support to open a bank account, (iii) tax mediation services. The study included 3,600 informal businesses operating with a fixed location in Cotonou, Benin, which were randomly allocated between three treatment groups and one control group. One year after the program launch, all versions of the program had significant impact on formalization rates. The impact was 9.1 percentage points in the first treatment group; 13 percentage points in the second group; and 15.8 percentage points in the last group. The program had a higher impact on male business owners, with more education, operating outside Dantokpa Market, in sectors other than trade, and that before being offered the incentives to formalization had characteristics similar to businesses that were already formal. Data from a second follow-up survey, which is expected to take place in March 2016, will explore the impacts on other outcomes, like business performances or access to banking.